2017
DOI: 10.1080/13607863.2017.1339779
|View full text |Cite
|
Sign up to set email alerts
|

Tea consumption is associated with cognitive impairment in older Chinese adults

Abstract: Habitual tea consumption is suggested to be associated with a decreased risk of CoI among elders in Suzhou, and a higher frequency of tea consumption was associated with a lower prevalence of CoI among never smokers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 42 publications
4
18
0
Order By: Relevance
“…In a study conducted in Japan by Kuriyama et al [180] in a group of 1003 persons aged > 70 years, it was demonstrated that the incidence of cognitive disorders was lower in persons consuming more green tea. Additionally, a study conducted in China among subjects aged over 65 years revealed a negative correlation between consumption of green tea and incidence of cognitive disorders [181]. Similar results were reported in Norway [182] and Singapore [183].…”
Section: Antioxidative Therapies In Neurodegenerative Diseases-clinicsupporting
confidence: 61%
“…In a study conducted in Japan by Kuriyama et al [180] in a group of 1003 persons aged > 70 years, it was demonstrated that the incidence of cognitive disorders was lower in persons consuming more green tea. Additionally, a study conducted in China among subjects aged over 65 years revealed a negative correlation between consumption of green tea and incidence of cognitive disorders [181]. Similar results were reported in Norway [182] and Singapore [183].…”
Section: Antioxidative Therapies In Neurodegenerative Diseases-clinicsupporting
confidence: 61%
“…Other studies reported by Nurk et al in Norway and Feng et al in Singapore also demonstrated similar associations [ 71 , 72 ]. Recently, Gu et al reported the same trend in a Chinese population aged ≥60 years [ 73 ]. However, one study resulted in no significant association between green tea consumption and cognitive impairment [ 74 ], and another study showed sex differences within the effects [ 75 ].…”
Section: Clinical Studies On Catechins and Admentioning
confidence: 59%
“…In fact, many researchers failed to report on the physical and social health that is linked with cognitive decline during the follow-up period [7][8][9][10]. However, the association between smoking and cognitive decline is still in the debate and controversial [8,9]. Therefore, the present study aim at the prospective study of the elderly Chinese Community population to assess the association between alcohol consumption and smoking and cognitive decline during a 6 year study period.…”
Section: ------------------------------------------------------------mentioning
confidence: 95%
“…Although many studies have reported on the health effects related to smoking and alcohol consumption and its association with cognitive decline, several studies lack to focus and report on the gender differences [7][8][9]. In fact, many researchers failed to report on the physical and social health that is linked with cognitive decline during the follow-up period [7][8][9][10]. However, the association between smoking and cognitive decline is still in the debate and controversial [8,9].…”
Section: ------------------------------------------------------------mentioning
confidence: 99%